2021
DOI: 10.1177/0192513x211010206
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, Fear of Intimacy, and Relationship Satisfaction

Abstract: Alexithymia, fear of intimacy, attachment security, and mood variables were examined as predictors of satisfaction in couple relationships after accounting for age, sex, relationship length, and marital status. Participants were 158 adults (52% women and 48% men) in an ongoing couple relationship for 1-19 years. They completed validated measures of the variables of interest online. Bivariate correlations were significant for all predicted associations. Multiple mediation modelling examined the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Such findings fit with other work indicating that alexithymia tends to be associated with an avoidant attachment style (Besharat et al, 2014;Spitzer et al, 2005), an anxious attachment style (Thorberg et al, 2011b), or features of both (Szpak & Bialecka-Pikul, 2015). Not surprisingly then, alexithymia is also associated with self-reported loneliness and persistent interpersonal difficulties (Besharat et al, 2014;Gilbert, 2010;Lyvers et al, 2021;Qualter et al, 2009;Spitzer et al, 2005;Vanheule et al, 2007). Thus, a major resource for coping with distressi.e., social support -may not be available to highly alexithymic individuals, or even if available they may be reluctant to access such support given their wariness about trusting and depending upon others, as well as fears of intimacy and rejection.…”
supporting
confidence: 88%
“…Such findings fit with other work indicating that alexithymia tends to be associated with an avoidant attachment style (Besharat et al, 2014;Spitzer et al, 2005), an anxious attachment style (Thorberg et al, 2011b), or features of both (Szpak & Bialecka-Pikul, 2015). Not surprisingly then, alexithymia is also associated with self-reported loneliness and persistent interpersonal difficulties (Besharat et al, 2014;Gilbert, 2010;Lyvers et al, 2021;Qualter et al, 2009;Spitzer et al, 2005;Vanheule et al, 2007). Thus, a major resource for coping with distressi.e., social support -may not be available to highly alexithymic individuals, or even if available they may be reluctant to access such support given their wariness about trusting and depending upon others, as well as fears of intimacy and rejection.…”
supporting
confidence: 88%
“…Alexithymic individuals find difficult to understand their partners' emotions, to communicate their emotional needs and to provide emotional support, potentially leading to conflict and dissatisfaction (Lyvers et al, 2021). Although this study brings alexithymia as an important factor in satisfaction level in relationships, other aspects should be considered, such as the ability to resolve conflicts and receptivity.…”
Section: Discussionmentioning
confidence: 85%
“…Mediated by the fear of intimacy, alexithymia is associated with attachment insecurity, and may create a barrier to interpersonal relationships. (Lyvers et al, 2017;Lyvers et al, 2021). Perchance, men with less difficulty of expressing emotions are more likely to remain in lasting relationships and reach higher levels of sexual satisfaction with their partners.…”
Section: Discussionmentioning
confidence: 99%
“…The negative body-experience and sorrow associated to an impossibility to naturally conceive, might lead women to be more emotionally detached that they would otherwise be, as attempt to contain such negative experiences with consequences on the couple's relationship. In this regard, the alexithymia construct, a personality trait that describes a difficulty in understanding and communicating feelings and emotional states (Sifneos 1973;Taylor and Bagby 2012), might be of relevance, particularly since greater negative affects mediate the association between alexithymia and reduced relationship quality (Lyvers et al, 2021). Yet, alexithymia seems more relevant for males (Conrad et al, 2001;Simionescu et al, 2021), which is in line with the above-mentioned greater avoidant attachment observed among males and defined by aloofness and an emotional detachment from the relationship (Donarelli et al, 2012;Moura-Ramos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%